Ultrasound-based risk model for preoperative prediction of lymph-node metastases in women with endometrial cancer: model-development study - Eriksson, L S E; Epstein, E; Testa, A C; Fischerova, D; Valentin, L; Sladkevicius, P; Franchi, D; Frühauf, F; Fruscio, R; Haak, L A; Opolskiene, G; Mascilini, F; et al. (Ultrasound in obstetrics & gynecology, 2020)
OBJECTIVE: To develop a preoperative risk model, using endometrial biopsy results and clinical and ultrasound variables, to predict the individual risk of lymph-node metastases in women with endometrial cancer. METHODS: A mixed-effects logistic regression model for prediction of lymph-node metastases was developed in 1501 prospectively included women with endometrial cancer undergoing transvaginal ultrasound examination before surgery, from 16 European centers. Missing data, including missing lymph-node status, were imputed. Discrimination, calibration and clinical utility of the model were evaluated using leave-center-out cross validation. The predictive performance of the model was compared with that of risk classification from endometrial biopsy alone (high-risk defined as endometrioid cancer Grade 3/non-endometrioid cancer) or combined endometrial biopsy and ultrasound (high-risk defined as endometrioid cancer Grade 3/non-endometrioid cancer/deep myometrial invasion/cervical stromal invasion/extrauterine spread). RESULTS: Lymphadenectomy was performed in 691 women, of whom 127 had lymph-node metastases. The model for prediction of lymph-node metastases included the predictors age, duration of abnormal bleeding, endometrial biopsy result, tumor extension and tumor size according to ultrasound and undefined tumor with an unmeasurable endometrium. The model's area under the curve was 0.73 (95% CI, 0.68-0.78), the calibration slope was 1.06 (95% CI, 0.79-1.34) and the calibration intercept was 0.06 (95% CI, -0.15 to 0.27). Using a risk threshold for lymph-node metastases of 5% compared with 20%, the model had, respectively, a sensitivity of 98% vs 48% and specificity of 11% vs 80%. The model had higher sensitivity and specificity than did classification as high-risk, according to endometrial biopsy alone (50% vs 35% and 80% vs 77%, respectively) or combined endometrial biopsy and ultrasound (80% vs 75% and 53% vs 52%, respectively). The model's clinical utility was higher than that of endometrial biopsy alone or combined endometrial biopsy and ultrasound at any given risk threshold. CONCLUSIONS: Based on endometrial biopsy results and clinical and ultrasound characteristics, the individual risk of lymph-node metastases in women with endometrial cancer can be estimated reliably before surgery. The model is superior to risk classification by endometrial biopsy alone or in combination with ultrasound. Copyright © 2019 ISUOG. Published by John Wiley & Sons Ltd.
Keywords: diagnostic imaging; lineární modely; Carcinoma, Endometrioid; Sensitivity and Specificity; senzitivita a specificita; ultrasonography; Humans; lidé středního věku; kohortové studie; Female; Aged; rizikové faktory; dospělí; Endometrial Neoplasms; Ultrasonography; senioři; lidé; Lymphatic Metastasis; lymfatické metastázy; Cohort Studies; Adult; Lymph Nodes; staging nádorů; endometroidní karcinom; ženské pohlaví; lymfatické uzliny; ultrasonografie; Middle Aged; Linear Models; Aged, 80 and over; decision support model; neoplasm staging; senioři nad 80 let; nádory endometria; Neoplasm Staging; lymphatic metastasis; prospektivní studie; endometrial neoplasm; Risk Factors; Prospective Studies